3D Nonlinear Parallel FEM for Analyzing Dynamic Response of the Large- Scale Saturated Soil Layers-Civil Structures Interaction Problem (Part I: Formulation and its Numerical Solution) - Tanjung, Jafril (Institut Teknologi Bandung, 2010)
Abstract. In this analytical study a 3D nonlinear parallel FEM algorithm was developed to overcome the physical limitation of a single processor computer when analysing the dynamic response of interaction between a large-scale saturated soil layers and civil structures. The parallel algorithm was derived based on the Domain Decomposition Method (DDM) such that a boundary value problem can be converted into an interface problem. The DDM was used to partite a whole of analytical domain into several non-overlapping subdomains. One feature of the current algorithm is most parts of the computation processes are performed in subdomain basis without interprocessor communication. The interprocessor communication is only take place when solving the interface problem. An iterativesolver of the Conjugate Gradient (CG) algorithm incorporating with the interprocessor communication based on hypercube networking was used to solve it interface problem. Abstrak. Dalam studi analitik ini, algoritma paralel elemen hingga non-linier dikembangkan untuk mengatasi kelemahan dari kemampuan komputer berprosesor tunggal dalam menganalisis tanggap dinamik pada masalah interkasi antara lapisan tanah jemuh dan struktur sipil dalam skala besar. Algoritma paralel dijabarkan berdasarkan motode dekomposisi domain untuk mengubah masalah nilai batas ke masalah interfes. Metode dekomposisi domain digunakan untuk membagi keseluruhan domain yang dinalisis menjadi beberapa subdomain yang tidak saling overlap. Keungulan dari algiritma yang dikembangkan ini adalah sebagian besar proses perhitungan dilakukan dalam basis subdomain tanpa adanya komunikasi antar prosesor. Komunikasi antar prosesor hanya dilakukan ketika menyelesaikan masalah interfes. Metode iteratif Conjugate Gradient, yang digabungkan dengan komunikasi antar prosesor berbasiskan jejaring hypercube, digunakan untuk menyelesaikan masalah interfes tersebut.